Controlling the stereostructure of non‐planar ring to induce the transition from plastic to elastomer in poly(butylene adipate‐co‐1, 4‐cyclohexane dicarboxylate) and implement of polylactic acid toughness. Issue 12 (30th January 2017) - Qiu, Jia; Liu, Fei; Zhang, Junwu; Chen, Jing; Na, Haining; Zhu, Jin
Abstract : The controllable polyesters with high overall performance are obtained by tuning the stereostructure of 1, 4‐cyclohexylene ring moieties (CHRMs) in poly(butylene adipate‐ co −1, 4‐cyclohexanedicarboxylate) (PBAC). After increasing the number of irregular cis ‐CHRMs in the polyester, PBAC can transform from semicrystalline polymer to amorphous one. PBAC with 58% cis ‐CHRMs starts to exhibit good elasticity with shape recovery of 60% at 250% deformation, indicating the transition from plastic to thermoplastic elastomer. Through blending with polylactic acid (PLA), the elastic PBAC greatly enhances the impact strength of PLA to 7.5 kJ/m 2 . While the tensile elongation at break is dramatically improved to 161% with the addition of plastic PBAC. The mechanism related to the stereostructure of non‐planar ring of PBAC on the properties of PLA is also analyzed. Therefore, this research suggests a particular way to build non‐planar ring contained polyesters to modify PLA with high toughness. POLYM. ENG. SCI., 57:1277–1284, 2017. © 2017 Society of Plastics Engineers